Announcements Effect of Corporate Bond Issuance and Its Determinants - Sze Kim Chin; Nur Adiana Hiau Abdullah (Contemporary Economics, 2013)
This study aims to investigate the effect of bond issuance announcements and to determine the company characteristics that could influence this effect. The findings reveal positive cumulative average abnormal returns following bond issuances, indicating that the market considers bond offers to be favorable news. Nevertheless, cross-sectional regression analysis shows an insignificant relation of company profitability, growth opportunities, asset tangibility, size, and managerial ownership with cumulative abnormal returns. The results confirm that there is a signaling effect of bond issuance announcements and that this effect is not affected by company characteristics.